Natural infection of Neotropical bats with hantavirus in Brazil - Sabino-Santos, Gilberto; Motta Maia, Felipe Goncalves; Martins, Ronaldo Braganca; Gagliardi, Talita Bianca; Souza, William Marciel de; Muylaert, Renata Lara [UNESP]; Souza Luna, Luciano Kleber de; Melo, Danilo Machado; Cardoso, Ricardo de Souza; Barbosa, Natalia da Silva; Pontelli, Marjorie Cornejo; Mamani-Zapana, Priscila Rosse; et al. (Nature Publishing Group, 2018)
Bats (Order: Chiroptera) harbor a high diversity of emerging pathogens presumably because their ability to fly and social behavior favor the maintenance, evolution, and dissemination of these pathogens. Until 2012, there was only one report of the presence of Hantavirus in bats. Historically, it was thought that these viruses were harbored primarily by rodent and insectivore small mammals. Recently, new species of hantaviruses have been identified in bats from Africa and Asia continents expanding the potential reservoirs and range of these viruses. To assess the potential of Neotropical bats as hosts for hantaviruses and its transmission dynamics in nature, we tested 53 bats for active hantaviral infection from specimens collected in Southeastern Brazil. Part of the hantaviral S segment was amplified from the frugivorous Carollia perspicillata and the common vampire bat Desmodus rotundus. DNA sequencing showed high similarity with the genome of Araraquara orthohantavirus (ARQV), which belongs to one of the more lethal hantavirus clades (Andes orthohantavirus). ARQV-like infection was detected in the blood, urine, and organs of D. rotundus. Therefore, we describe a systemic infection in Neotropical bats by a human pathogenic Hantavirus. We also propose here a schematic transmission dynamics of hantavirus in the study region. Our results give insights to new, under-appreciated questions that need to be addressed in future studies to clarify hantavirus transmission in nature and avoid hantavirus outbreaks.